The Development of Inquiry-Oriented Google Sites Learning Media to Improve Students' Science Process Skills - Nurani, Dwi Cahaya; Adikara, Fahmi Surya; Hartono, Hartono; Safitri, Mazda Leva Okta; Savitri, Dewinta Aulia (Universitas Pendidikan Indonesia, 2024)
This research aims to develop a Google Sites learning media that is oriented towards inquiry learning and is used to improve science process skills in students by testing its validity, practicality, effectiveness, and influence on improving science process skills. The research method used is RD, or development. The research model applied is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The validation results obtained from media experts show a percentage of 97.5% or are included in the very valid category. Assessment by material expert validators shows a percentage of 97.5%, which is in the very valid category. Meanwhile, the assessment by language expert validators shows a percentage of 100% or very valid. Media practicality was obtained through a questionnaire that was assessed by fourth-semester students of Primary School Teacher Education FKIP Sriwijaya University with a percentage of 89%, which could be categorized as very practical. Furthermore, to measure effectiveness, it is done by comparing the scores obtained from student observations based on 14 indicators of science process skills before using learning media with a percentage of 41% and after using Google Sites learning media oriented towards inquiry learning with a percentage of 89%, or an increase of 48%, or including them in the effective category. Based on this description, it shows that the Google Sites learning media oriented towards inquiry learning is valid, practical, and effective to use and has an influence on improving science process skills in students.